Registro de Plagiometriona clavata (Fabricius 1798) (Coleoptera: Chrysomelidae) en chile silvestre Capsicum annuum, de Baja California Sur, México - Tejas, R. A.; Servín, R.; Nieto-Garibay, A.; Marín, A. (Instituto de Ecología, A.C., 2011)
Plagiometriona clavata Fabricius, 1798 is reported for the first time on Capsicum annuum var. aviculare, considerated like the wild progenitor of the cultivated chiles.